Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1093/rheumatology/32.12.1077
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effect of Combined Naproxen and Paracetamol in Rheumatoid Arthritis

Abstract: The clinical effect and plasma naproxen levels were studied in 20 patients with RA receiving three doses of naproxen and two naproxen doses combined with paracetamol (acetaminophen) in a randomized, double-blind, comparison in five 2-wk treatment periods. A significant dose-concentration effect relationship was found for the three naproxen doses (500, 1000 and 1500 mg daily). The following variables were measured: global clinical effect, joint index, morning stiffness, activity of daily living (ADL), pain duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 0 publications
1
18
0
1
Order By: Relevance
“…ketoprofen, dexketoprofen (Miranda et al 2006(Miranda et al , 2007Luccarini et al 2006;Seideman 1993;Schug 2006;Qiu et al 2007). The synergic interaction was observed in the two nociceptive tests and, on the basis of the interaction indexes (Table 2), was stronger in Phase I of the formalin orofacial test.…”
Section: Discussionmentioning
confidence: 99%
“…ketoprofen, dexketoprofen (Miranda et al 2006(Miranda et al , 2007Luccarini et al 2006;Seideman 1993;Schug 2006;Qiu et al 2007). The synergic interaction was observed in the two nociceptive tests and, on the basis of the interaction indexes (Table 2), was stronger in Phase I of the formalin orofacial test.…”
Section: Discussionmentioning
confidence: 99%
“…At low doses and even with long administration, their role as DMARDs is gaining ground. Its beneWt is because of its anti-inXammatory eVect [7,56,57], NSAIDs due to their analgesic, anti-inXammatory and antipyretic eVect [7,[10][11][12][13], paracetamol due to its analgesic and antipyretic eVect [58,59] and amitriptyline due to its beneWt in depression and neuropathic pain [60,61] have all found a place in the treatment of rheumatoid arthritis as supportive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Nonacidic analgesics such as paracetamol, propyphenazone and dipyrone are poor inhibitors of pros taglandin synthesis and do not accumulate in the mucosa, which probably accounts for their greater tolerability [9], In addition, paracetamol has proved to be effective in lowering the analgesic dose of NSAID required, even in rheumatoid arthritis, for patients with gastrointestinal disturbances [10], Dipyrone has been shown to be an effective analgesic for a wide variety of indications, but very few data are available concerning its gastrointestinal toxicity. Despite the epidemiological evidence for the good gastrointestinal tolerability of dipyrone, direct ef fects of dipyrone (metamizole) on the gastrointestinal tract in humans have not yet been investigated in detail even if it has been shown that the ulcerogenic activity of dipyrone in rats is similar to that of paracetamol [11].…”
mentioning
confidence: 99%